ANALISA APLIKASI PENGHAFAL DOA – DOA ISLAM BERBASIS ANDROID UNTUK MENINGKATKAN MINAT BELAJAR SANTRI MANDRASAH DINIYAH - Ulum, Misbaul; Idris, Muhammad (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2019)
Prayer is part of all religious communities and especially for Muslims. Prayer is usually taught from an early age so that it is easy to memorize. And basically the prayer in Islamic religion is obligatory according to the word of Allah SWT. (Surah Al-A'raf: 55). In this digital era, technology has been greatly facilitated by existing technology because from what used to be prayer only in books, there is now an application that provides various prayer content that is attractively packed. This memorization application is made with the Android Studio application which is an application tool for developing android applications. In addition, there are several programming languages that must be mastered in making applications, Java, Html5, and Css3. In the system development method, researchers use the Waterfall method because this method is very suitable for making an application. Due to the limited knowledge of researchers in making applications, this time the application can only be opened online and cannot be opened offline. From the results of this study the application of memorizing prayer is interesting and has features of prayer reading, audio prayer, video prayers whose contents are very interesting to read and play.